USING VIRTUAL REALITY DEVICE AS AN INNOVATIVE STRATEGY TO TEACH VOCABULARY FOR TOURISM STUDENTS - I Nengah Laba; Astawa, I Gede; Sonder, I Wayan (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT AKADEMI PARIWISATA DENPASAR, 2020)
This study aimed at figuring out the effectiveness of using virtual reality device to teach vocabulary for students. Virtual reality device is a tool that can show an interactive media in 3D images and sounds combined with the virtual real-world. The data was collected through journal articles or library research. The result of the library research showed that virtual reality device is effective to teach vocabulary for students. From the library was also found that there are thirteen advantages or impacts in conducting virtual reality device in tourism classroom. It was also found that the steps in conducting virtual reality strategy is easy to be implemented and can be done by the teacher properly. It implies the use of virtual device in the classroom will helpful for teacher and students